PENGARUH LAYANAN BIMBINGAN KELOMPOK MENGGUNAKAN MEDIA FILM TERHADAP PERILAKU AGRESIF - Rahmaliana Saputri; Satrio Budi Wibowo; Achmad Irfan Muzni (Counseling Milenial (CM), 2024)
This research is quantitative. The purpose of this study was to determine the effect of group counseling services using film media on aggressive behavior in students at SMP Negeri 2 Kotagajah. This study used a sample of 10 students who had aggressive behavior. Samples were given a pretest and posttest to find out whether the service had an effect or not in the research process. Group guidance services were carried out three times with the second service using film media. The results of the hypothesis calculations using JASP showed significant results as seen from the results of the Paired Samples T-test using the Wilcoxon signed rank test which was significant between the pretest and posttest values with p = 0.004, <0.05. Thus H0 is accepted and Ha is rejected and there is a difference. This means that in this study group guidance using film media was effectively used to reduce aggressive behavior and there was a significant influence between the independent variables on the dependent variable.